Secular stagnation: a tough test for the post-growth economy. (2nd June 2023) - Oberholzer, Basil
Historically, economic growth has gone along with increasing resource consumption and environmental pollution. On the other hand, periods of low growth have involved social hardship. This growth dilemma is confronted with an actual decline in current economic growth in industrial countries. The period of so-called 'secular stagnation' intensifies the threats of unemployment, wage pressure, and deteriorating living conditions. Policy strategies that make the economy independent of the growth imperative to reduce resource consumption while maintaining a high quality of life require macroeconomic governance. This article provides an overview of the main policy proposals to avoid secular stagnation to argue that tackling the growth dilemma requires the macroeconomic management of the drivers of growth, that is, effective demand and profitability. The contradiction between these two growth drivers becomes ever more prevalent in the age of secular stagnation and reveals the analytical gaps ecological economics research should focus on.